Capital controls, banking competition, and monetary policy. - Ghossoub, Edgar A.; Harrison, Andre; Reed, Robert R. (Economic Inquiry, 2024)
How do capital controls and banking concentration affect economic development? This paper develops a general equilibrium model to study these important issues. To do so, we construct a framework with heterogeneous agents and imperfectly competitive financial intermediaries who help depositors manage liquidity risk. Importantly, higher levels of concentration raise the cost of domestic borrowing which increase the reliance on international capital markets. Finally, once the rate of money growth is sufficiently high, capital controls bind and the effects of monetary policy on capital formation are more pronounced.